Fecal Bacteria as Non-Invasive Biomarkers for Colorectal Adenocarcinoma - Yuan, Biao; Ma, Bin; Yu, Jing; Meng, Qingkai; Du, Tao; Li, Hongyi; Zhu, Yueyan; Sun, Zikui; Ma, Siping; Song, Chun (Frontiers in Oncology, 2021)
Colorectal adenocarcinoma (CRC) ranks one of the 5 most lethal malignant tumors both in China and worldwide. Early diagnosis and treatment of CRC could substantially increase the survival rate. Emerging evidence have revealed the importance of gut microbiome on CRC, thus fecal microbial community could be termed as a potential screen for non-invasive diagnosis. Importantly, few numbers of bacteria genus as noninvasive biomarkers with high sensitivity and specificity causing less cost would benefit more in clinical, compared with the whole microbial community analysis. Here we analyzed the gut microbiome between CRC patients and healthy people using 16s rRNA sequencing showing the divergence of microbial composition between case and control. Furthermore, ExtraTrees classifier was performed for the classification of CRC gut microbiome and heathy control, and 40 bacteria were screened as biomarkers for CRC. In addition, the combination of 40 biomarkers and FOBT showed an outstanding sensitivity and specificity for discrimination CRC patients from healthy controls. This method could be used as a non-invasive method for CRC early diagnosis.